Awareness and Perception of Educated Consumers about Consumer Protection Laws - Basavaraj, C.S; Tangade, Shrimant F. (Indian Journal of Marketing, 2004)
A consumer is one who buys any goods or services, by paying its price, either for his own consumption or for his livelihood. Therefore, every body is a consumer in one or the other way. Philosophers and thinkers have regarded consumer as the base of every business. No business activities move in the country without the presence of consumers. But still it is a common practice that businessmen exploit the consumers as regards to quality, quantity, weight, price and other related factors involved in the daily business transactions. It was estimated that "The Indian consumer is being cheated by about Rs. 2000 crores every year". Legal environment is the most important factor in protecting the interests of the consumers. If proper support of law does not exist, the consumer cannot be defended in the court of law. For the protection of consumers, from time to time, the Government of India has enacted several laws. Presently there are more than 20 laws in the country either directly or indirectly protecting the interests of the consumers. But the million Dollar question is whether Indian consumers have the knowledge about these laws? Are they able to get benefit under these laws by exercising their rights, given under the respective Acts? The researchers try to answer these questions through the present paper.